Comparison of prophylactic versus regular use of antibiotics in elective major obstetrical and gynecological surgeries - Sundharam, Ramya Sreevarshni Shunmugha; P. B., Hiremath; R., Sankareswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Surgical site infections better prevented by parenteral antibiotic in sufficient doses generally should be given before the operation which helps to achieve the therapeutic drug level both in the blood and related tissue during the operation. Ceftriaxone, when administered together as a prophylaxis can fulfil the above criteria of a good antibiotic. Thus, this study was planned to assess the efficacy of prophylactic antibiotic usage to that of regular antibiotics usage in patients undergoing elective surgeries. Methods: This randomized controlled study was conducted in a tertiary care teaching hospital during the study period of June 2017 to April 2018 with 140 cases. Group A received a single dose of Injection Ceftriaxone 1g. Group B, received Injection Ceftriaxone 1 gm and Injection Metronidazole 500 mg for five days. The data was entered in excel sheet and analyzed using SPSS (Version 16). Results: The mean age group in Group A and Group B was found to be 34.24±10.5 and 35.97±11.89, respectively. There was no statistical significance between group A and B for incidence of infection in the post-operative period and duration of hospital stay. The mean value in group A for duration of surgery was found to be 67.5±13.5 and in group B mean value was 72.1±14.9. (p value <0.05). Conclusions: This study demonstrated that administration of prophylactic antibiotic rather than conventional antibiotic at caesarean and gynecological surgeries are not associated with significant difference in post-operative morbidities.